If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-6-4=3(n+2)
We move all terms to the left:
5-6-4-(3(n+2))=0
We add all the numbers together, and all the variables
-(3(n+2))-5=0
We calculate terms in parentheses: -(3(n+2)), so:We get rid of parentheses
3(n+2)
We multiply parentheses
3n+6
Back to the equation:
-(3n+6)
-3n-6-5=0
We add all the numbers together, and all the variables
-3n-11=0
We move all terms containing n to the left, all other terms to the right
-3n=11
n=11/-3
n=-3+2/3
| 9x/2-4=12 | | 202=43-v | | 8+5(-8x+1)=2 | | 0.03x+0.32=0.05x-0.74 | | 175m-125m+47500=50750-200m | | -2/5m+3=2/3m+1/3 | | 4f=1 | | -6x+7+8x=4 | | (3v–2)(4v+4=) | | a^2+7a-140=0 | | 9x+7=12x+37 | | -7x+10+2x=30+5x+28 | | 5p+12=7p+18 | | 6x-13-4x-13=6 | | 15/7h=25 | | 9-2x-54x=4 | | (500)(12)x=1600 | | 4(2x-3)-5x-3=-2 | | 12k+6=4k−8 | | -a=34 | | Y=-2/5x-6 | | -4(-3t+1)-7t=5t+4 | | f+50=555 | | 11v-3v=54 | | -2x(x-4)-12=8 | | (3x-8)/5=-4 | | x(x-4)-12=8 | | 52a+4=-100 | | 5(7x-2)+2x=-5 | | 2x=7x+27 | | 3/5(25x-10)=519 | | -6c-7+6.5c-12=-11 |